The Internalization of Religious Moderation Values in Pesantren in Central Kalimantan - Aliyah, Muhimmatul; Lestari, Mega Asri; Langputeh, Sukree; Langputeh, Muslim; Ahmadi; Ajahari (Faculty of Ushuluddin, Adab, and Da'wah, State Islamic University of Palangkaraya, 2024)
The article aims to analyze the internalization of religious moderation values in Pesantren in Central Kalimantan. This article is a qualitative study with a case study approach. The study focuses on three Pesantrens: Pesantren Sabilal Muhtadin in East Kotawaringin, Pesantren Hidayatul Insan in Palangka Raya City, and Pesantren Nahdatus Salam in Kapuas. Data were collected through interviews, observations, and documentation. Data collection was conducted from May to October 2024. The data obtained were analyzed using the Miles and Huberman analysis model: data reduction, data display, and conclusion. The data obtained shows that the internalization of religious moderation is rooted in the Pesantren tradition in Central Kalimantan and has been practiced before becoming a strategic program of the Ministry of Religious Affairs in 2019. In this context, the experience of inter-ethnic conflict in 2001 was a background factor in consistently internalizing religious moderation. In addition, internalization is also carried out as a preventive effort from being exposed to extremist movements and intolerant ideology. Internalization efforts are carried out using various strategies that adapt to the socio-cultural setting of each pesantren.